Ghost Wars: The Secret History of the CIA, Afghanistan and Bin Laden, From the Soviet Invasion to September 10, 2001 - Coll, Steve (GHQ, Rawalpindi Army Publishing House, 2010)
The explosive first-hand account of America's secret history in Afghanistan With the publication of Ghost Wars, Steve Coll became not only a Pulitzer Prize winner, but also the expert on the rise of the Taliban, the emergence of Bin Laden, and the secret efforts by CIA officers and their agents to capture or kill Bin Laden in Afghanistan after 1998.
Include Index
Keywords: Afghanistan -- History -- Soviet occupation, 1979-1989. -- Afghanistan -- History -- 1989-2001. -- United States. -- Central Intelligence Agency